Teachers’ Perceptions of the Continuous Assessment System: Opportunities and Challenges - Bista, Nar Bahadur; Bohara, Nirajan (Mangal Research Journal, 2025)
Individual student achievement is strongly influenced by the assessment practices adopted by teachers, as continuous assessment—an assessment for learning—provides regular feedback that supports ongoing improvement. This study employed a qualitative research design to explore teachers’ perceptions of the Continuous Assessment System (CAS) in basic-level schools. Semi-structured interviews were conducted with four purposively selected primary-level teachers who regularly practiced CAS in their classrooms. The data were analysed thematically under two major themes: the opportunities offered by CAS and the challenges encountered in its implementation. The findings revealed that teachers perceived CAS as supportive for continuous monitoring of students’ progress, identifying learning gaps, providing individualized feedback, and fostering creativity, critical thinking, and active engagement. However, teachers also faced several practical challenges, including heavy workload, large class sizes, lack of formal training, insufficient time for documentation, and limited provision for remedial teaching. The study concludes that although CAS holds strong formative and pedagogical potential for improving learning in early grades, its effective implementation requires adequate teacher training, manageable teaching loads, and stronger institutional support to align classroom practice with policy expectations.